Noncoding Transcribed Ultraconserved Region (T-UCR) uc.261 Participates in Intestinal Mucosa Barrier Damage in Crohn's Disease. Issue 12 (December 2016) - Qian, Xiao Xian; Peng, Jiang Chen; Xu, An Tao; Zhao, Di; Qiao, Yu Qi; Wang, Tian Rong; Shen, Jun; Ran, Zhi Hua
Abstract : Background: To date, 481 ultraconserved regions (UCRs) have been discovered in human genome. We aimed to investigate the transcribed UCR (T-UCR) characteristics in Crohn's disease (CD ) and determine whether T-UCR uc.261 participated in intestinal mucosa barrier damage. Methods: T-UCRs were screened in active CD mucosa using the Arraystar Human T-UCR Microarray and validated with quantitative real-time reverse transcription PCR, together with tight junction proteins (TJPs) including junctional adhesion molecule–A, occludin, claudin-1, and zonula occluden–1. T-UCR uc.261 in active CD mucosa was validated by RNA fluorescence in situ hybridization. Caco2 and T84 cells were employed to determine transepithelial electrical resistance. Cdc42, protein kinase C ζ, PAR3, and PAR6 were assessed with quantitative real-time reverse transcription PCR and Western blotting. The assembly of TJPs was detected using cell immunofluorescence assay. Results: Four T-UCRs were significantly upregulated (uc.290−, uc.144−, uc.261−, and uc.477+) and 4 T-UCRs were downregulated (uc.166−, uc.141−, uc.478+, and uc.479+). Uc.261 was inversely correlated with transepithelial electrical resistance during tight junction formation. The levels of TJPs were diminished in active CD mucosa. Most uc.261s were located in the cytoplasm of colonic epithelial cells. Overexpression of uc.261 reduced transepithelial electrical resistance, inhibited the expression and assembly of TJPs, activated Cdc42, and suppressed protein kinase C ζ. Silencing of uc.261 in TNF-α–treated cells reversed the tight junction damage. Conclusions: Overexpression of uc.261 participates in intestinal mucosa barrier damage. Suppression of uc.261 reverses the damage to tight junction in inflammation. Attenuation of uc.261 overexpression might be a rational strategy to manage patients with CD. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 8 November 2016.